От древнейших времен до середины XIX века - Левашева Ольга Евгеньевна (1980)
Экземпляры: ИСК (20120817) / Инвентарный номер: 733911 / Цена: 1.90 / Сис.шифр: 85.313(2Р=Рус) / Авт.знак: И 90 / ГРНТИ: 18 / ББК: 85.313(2Р=Рус)